Direct shear failure in concrete joints exposed to elevated temperatures. (October 2020) - Ahmad, Subhan; Bhargava, Pradeep; Chourasia, Ajay
Abstract: Push off type specimens were tested to study the impact of different elevated temperatures on the shear capacity of concrete. Specimens fabricated with concrete of 40 MPa were exposed to heating in an electric furnace up to 350, 550, and 750 °C. Heated samples were cooled naturally up to the room temperature. Results of the unheated and heated specimens revealed that exposure temperatures of 350, 550, and 750 °C reduced the shear capacity of concrete by 18.85, 29.6, and 52.74%, respectively. A simplified method was also suggested for the computation of the shear capacity of concrete after elevated temperatures. The proposed method provided precise estimates of the shear capacity of concrete exposed to high temperatures.